The Modification of a Tetrafunctional Epoxy and Its Curing Reaction - Yu, Mingming (Materials (Basel), 2015)
Recent experimental results showed that the T(g) of cured resin scarcely decreased and the impact strength of resins increased by over 50% when a tetrafunctional epoxy named N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenyl ether (TGDDE) was introduced to an appropriate flexible chain from a dimer fatty acid (DFA). In order to understand the reason for this phenomenon, the modification and the chemical structure of the prepolymer together with the curing reaction and the viscoelasticity of the cured resins were studied in detail in the present work. The results indicated that the modification would help the prepolymer improve its molecular mobility. As a result, the resins could be further cured, resulting in the cross-linking density increasing. This is because the curing efficiency was increased, but the tetrafunctional epoxy was not cured completely due to its large steric hindrance. Moreover, the flexibility of some parts of the networks was improved, which was beneficial for the toughness of the cured resins. Therefore, the toughness of the tetrafunctional resin was improved with little influence on the thermal properties when the epoxies were modified with an appropriate content of DFA.